Complete mitogenome of the Common Koel Eudynamys scolopaceus Linnaeus 1758 (Aves: Cuculidae). Issue 5 (4th May 2022) - Wang, Guohai; Tang, Chuangbin; Li, Jinlan; Huang, Qiuchan; Nong, Jialin; Wei, Lijuan; Zhou, Qihai
Abstract: The Common Koel Eudynamys scolopaceus Linnaeus 1758, belongs to the family Cuculidae and order Cuculiformes. This omnivorous bird exhibits obligate nest parasitism. Here, the complete mitogenome of E. scolopaceus was determined and phylogenetically compared with those of other Cuculidae species. The newly sequenced complete mitogenome was a circular DNA molecule with a size of 17, 610 bp (OM115963). This mitogenome had a higher A + T content (57.58%) than G + C content (42.42%). Phylogenetic analysis revealed that E. scolopaceus was most closely related to Eudynamys taitensis and the genus Cuculus, providing useful molecular information for further research on the phylogeny of the family Cuculidae.